Risk and return in international corporate bond markets - Geert Bekaert; Roberto A. De Santis (European Central Bank (ECB), 2020)
Corporate bond returns in the major developed economies increase with risk, as measured by maturity and ratings. From a pricing perspective, we find little to no evidence against the World CAPM model, where the market consists out of equity, sovereign and corporate bonds. However, from a factor model perspective, local factors contribute substantially more to the variation of corporate bond returns than global factors. The factor exposures show intuitive patterns: as ratings worsen, equity betas show a hockey stick pattern, sovereign betas decline monotonically and corporate bond betas increase steeply.
Keywords: G10; G11; G15; 330; Corporate bond markets; CAPM; international market integration; asset class integration; bond ratings; risk; return